Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 29 May 2017, 01:17

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If P# =P/P-1 what is P##? P/(P-1) 1/P P 2 - P P

Author Message
Senior Manager
Joined: 14 Jun 2007
Posts: 397
Followers: 1

Kudos [?]: 15 [0], given: 0

If P# =P/P-1 what is P##? P/(P-1) 1/P P 2 - P P [#permalink]

### Show Tags

23 Jun 2007, 14:29
00:00

Difficulty:

(N/A)

Question Stats:

100% (02:37) correct 0% (00:00) wrong based on 1 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

If P# =P/P-1 what is P##?

P/(P-1)
1/P
P
2 - P
P - 1

Senior Manager
Joined: 04 Jun 2007
Posts: 345
Followers: 1

Kudos [?]: 30 [0], given: 0

### Show Tags

23 Jun 2007, 22:27
anonymousegmat wrote:
If P# =P/P-1 what is P##?

P/(P-1)
1/P
P
2 - P
P - 1

p## = (p/(p-1))# = [p/(p-1)]/[[p/(p-1)]-1]=[p/(p-1)]/[1/(p-1)]=p
Senior Manager
Joined: 14 Jun 2007
Posts: 397
Followers: 1

Kudos [?]: 15 [0], given: 0

### Show Tags

24 Jun 2007, 09:31
sumande wrote:
anonymousegmat wrote:
If P# =P/P-1 what is P##?

P/(P-1)
1/P
P
2 - P
P - 1

p## = (p/(p-1))# = [p/(p-1)]/[[p/(p-1)]-1]=[p/(p-1)]/[1/(p-1)]=p

sumande,

thanks. i was trying to factor and do all sorts of weirdness; essentially we just replace each p with p/p-1

thats not so tough

i ended up with:

(p/p-1)# = p/p(1-(1/p))# = 1/(1-1/p)# 1- 1/(p/p-1) = -1/p
Director
Joined: 06 Sep 2006
Posts: 740
Followers: 2

Kudos [?]: 40 [0], given: 0

### Show Tags

24 Jun 2007, 14:42
P## = [ P#/(P#-1) ] ....X

P# = P/(P-1) -----A
So, P# - 1 = P/(P-1) - 1 = P - P + 1/(P-1)
P#-1 = 1/(P-1) .....B

Plugging A & B in X.

P## = [P/(P-1)] / [1/(P-1)]

= P/(P-1) * (P-1)

= P.

C.
24 Jun 2007, 14:42
Display posts from previous: Sort by

# If P# =P/P-1 what is P##? P/(P-1) 1/P P 2 - P P

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.